Risk relationship between leukocyte telomere length and constipation: a Mendelian randomization study - Zhenfei Chi; Xuesong Bai; Zhe Zhang; Zhe Zhang (Frontiers in Medicine, 2023)
ObjectiveSome epidemiological studies have investigated the associations between aging and constipation, yet their outcomes are inconclusive, so we strive to ascertain whether aging is the cause of constipation.MethodsWe conducted a two-sample Mendelian randomization (MR) analysis using publicly accessible genome-wide association study (GWAS) summary statistics. As a marker of cellular and biological aging, we employed 15 single-nucleotide polymorphisms as instrumental variables for leukocyte telomere length (LTL) as exposure and a GWAS for constipation in the Finnish database as an outcome. To select the instrumental variables strongly associated with the phenotype, we eliminated confounding factors and direct effects outcomes to determine the causal relationship of exposure factors on the outcome; the analysis was mainly performed using the random-effect inverse variance weighting method, MR-Egger, weighted median, and sensitivity analysis of the results.ResultsRandom effect inverse variance weighted odds ratio = 1.035 (95% CI 0.907–1.180), but p = 0.612, which was not statistically significant. Other statistical methods, such as MR-Egger and weighted median, also yielded non-significant results.ConclusionLTL as a proxy for aging does not necessarily indicate an increased likelihood of constipation. Further research is needed to explore the specific mechanisms of constipation.